2011
DOI: 10.1111/j.1365-4632.2010.04775.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitudes towards head lice infestation in Greece

Abstract: There is a trend towards the use of natural oils for either prevention or treatment. More needs to be done to promote public education and rational use of either pediculicides or non-pharmacological agents for pediculosis capitis infestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Until now, several studies have focused on parental knowledges and attitudes [18-20]. Our survey agrees with all these studies showing that parents often seek advice firstly from the apothecary, or relatives, or friends, and only after a failure from a physician.…”
Section: Discussionsupporting
confidence: 89%
“…Until now, several studies have focused on parental knowledges and attitudes [18-20]. Our survey agrees with all these studies showing that parents often seek advice firstly from the apothecary, or relatives, or friends, and only after a failure from a physician.…”
Section: Discussionsupporting
confidence: 89%
“…Magee found that pediculicide treatment products were applied up five times longer than was recommended. In addition, harsh chemicals such as bleach, alcohol, and kerosene have been used to eradicate head lice …”
Section: Resultsmentioning
confidence: 99%
“…[11,18,19] A study from Greece showed that there was a lack in knowledge about the 773 prevention and treatment of head lice among healthcare professionals. [20] Perceptions and beliefs of parents included confusion and worry and it was demonstrated that the educational level of parents inversely associated with positive cases. [18] Another study showed a gab in knowledge of parents about head lice infestation in children.…”
Section: Discussion:-mentioning
confidence: 99%